2015
DOI: 10.1016/j.ajhg.2015.02.009
|View full text |Cite
|
Sign up to set email alerts
|

A Large-Scale Genetic Analysis Reveals a Strong Contribution of the HLA Class II Region to Giant Cell Arteritis Susceptibility

Abstract: We conducted a large-scale genetic analysis on giant cell arteritis (GCA), a polygenic immune-mediated vasculitis. A case-control cohort, comprising 1,651 case subjects with GCA and 15,306 unrelated control subjects from six different countries of European ancestry, was genotyped by the Immunochip array. We also imputed HLA data with a previously validated imputation method to perform a more comprehensive analysis of this genomic region. The strongest association signals were observed in the HLA region, with r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
102
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 151 publications
(118 citation statements)
references
References 76 publications
(103 reference statements)
6
102
2
1
Order By: Relevance
“…Consistent with their equivalent effect sizes, these variants are in almost complete LD (r 2  = 0.99). However, the rs2476601 variant encodes an Arg620Trp substitution in the Lyp phosphatase associated with risk of multiple autoimmune diseases, including giant cell arteritis 18, 19. Although not consistently observed in candidate gene studies 20, 21, the association of rs2476601 with GPA/MPA is strongly supported by our data, and unlike most of the other significant associations observed, this allele's strength of association did not differ between the subgroups (Table 2).…”
Section: Resultssupporting
confidence: 73%
“…Consistent with their equivalent effect sizes, these variants are in almost complete LD (r 2  = 0.99). However, the rs2476601 variant encodes an Arg620Trp substitution in the Lyp phosphatase associated with risk of multiple autoimmune diseases, including giant cell arteritis 18, 19. Although not consistently observed in candidate gene studies 20, 21, the association of rs2476601 with GPA/MPA is strongly supported by our data, and unlike most of the other significant associations observed, this allele's strength of association did not differ between the subgroups (Table 2).…”
Section: Resultssupporting
confidence: 73%
“…In a study performed on GCA patients from Rochester, Minnesota, USA, it has been proposed a DRYF motif at positions 28-31 in the second hypervariable region (HVR2) of MHC class II as a risk factor for GCA development [25]. However, this result has not been confirmed in a recent meta-analysis [26] and in a multicenter immunochip study [27]. Further studies have also demonstrated an association between HLA-DRB1*04 and visual loss [28] and glucocorticoid resistance [29].…”
Section: Immunogeneticsmentioning
confidence: 42%
“…[13]), interpretation of these studies has been hampered by difficulties in achieving the required large sample sizes for derivation and replication data sets. The first large-scale GCA genetic study, using the ImmunoChip platform, was published in 2013, and confirmed HLA-DRB1*04, followed by PTPN22 rs2476601, as the strongest genetic risk factors for GCA [18]. The study also identified other putative risk loci for GCA involved in Th1, Th17, and Treg cell function.…”
Section: Genetic Studiesmentioning
confidence: 91%